ANALISIS CULTURE SHOCK DALAM KOMUNIKASI INTERKULTURAL PADA MAHASISWA RANTAU DI UNIVERSITAS PENDIDIKAN INDONESIA - Hilya Mulyasani; Firman Aziz; Ryan Ferdiana; Nahla Hanifa; Vanessa Anastasya (SOSFILKOM : Jurnal Sosial, Filsafat dan Komunikasi, 2025)
The increasing number of students choosing to live away from home for higher education leads to frequent interactions between individuals with diverse cultural backgrounds, and this diversity sometimes causes culture shock. This research aims to analyze the relationship, impact, and ways of coping with culture shock in intercultural communication among students living away from home at Universitas Pendidikan Indonesia (UPI) Bandung. Employing a descriptive method with a qualitative approach, data was collected through in-depth interviews with seven students living away from home who have diverse cultural backgrounds. The research results indicate that all informants experienced culture shock in various aspects, including language, speech intonation, social norms, weather, and daily habits. The main challenges in intercultural communication experienced were the use of language and speech intonation different from their original cultures. Although culture shock presents negative impacts such as emotional exhaustion and difficulty in communicating, respondents also felt positive impacts in the form of increased cross-cultural understanding, adaptability, and expanded relationships. The strategies for coping with culture shock and communication challenges implemented varied, ranging from establishing communication with close individuals and local residents to developing patient, open-minded, and adaptive attitudes.